Tendon Sheath Hemangioma - Dalei, Tushar Ranjan; Loya, Vijay Kumar (Journal of Hand and Microsurgery, 2019)
Hemangioma of the tendon sheath is an uncommon tumor—often slow-growing and misdiagnosed until final biopsy. We hereby report a 30-year-old woman who presented with pain and swelling of the wrist for 2 years, which was proven to be cavernous hemangioma of extensor tendon sheath.
Keywords: hemangioma; tendon sheath; wrist and hand